Knee kinematics changes with the point of application of the ground reaction force in the medio-lateral direction in a simulated alpine skiing - a pilot study - Supej, M.; Zorko, M.; Milankovic, L.; Babic, J.; Nemec, B. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Recently, the alpine ski width under the ski boot has increased significantly. This causes the point of application of the ground reaction force to move in the medial direction during turning, and as a consequence it may increase the torque acting on the knee joint. The aim of this study was to analyse how the kinematics of the knee joint adapts to the new torque situation when using wider skis in simulated skiing conditions.